A Report on the State of Biblical Scholarship in the Philippines: An Unexpected Virtual Rhizomatic Emergence of Cellphone-Social Media as the ‘Publishing House’ of the Mass - Jeong, Dong Hyeon (Currents in biblical research, 2026)
The Philippines has become one of the nations with the highest number of active daily users of social media in the world. From Facebook to TikTok, watching and making videos and clips through the cellphone is an irrefutable phenomenon that permeated various sectors of the Philippines. Amplified by the pandemic, this phenomenon manifested as well in redefining academic/religious publishing. Virtual grassroots religious communities are creating and publishing their worship service, Bible study, academic conference, daily devotion, and other religious and academic contents via the social media. Their work has created new rhizomatic connections whereby the lived realities of the mass and their instantaneous capacity to respond and co-create academic/religious contents have become an irrefutable re-emergence and reconfiguration of what is called ?publishing?. By doing so, the rhizomatic connections that emerged out of these publishing networks have elevated and made more visible the presence, voices, and concerns of those who were previously deemed unworthy of being published.